Special Issue of Sustainable Asia Conference 2014 - Ning Zhang (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue will consist of selected papers from the Sustainable Asia Conference (SAC) 2014, an international conference which was held in Nanchang, China, from April 23-25, 2014. SAC 2014 is a leading conference for presenting novel and fundamental advances in Sustainable Development issues in Asia. The purpose of the conference is for scientists, scholars, engineers, and students from universities and research institutes around the world to present ongoing research activities, so as to promote global research networking in the sustainable development area. This conference provides opportunities for the delegates to exchange new ideas and application experiences face to face, to establish research or business relations, and to find global partners for future collaboration. The scope of this Special Issue encompasses topics related to sustainable development and management at both the macro- and micro-levels in Asian countries.